Tabayyun as the Foundation of Digital Literacy Ethics: The Relevance of the Prophet’s Hadith in Countering Misinformation - Choiriyah, Kuni Nurol (Maliki Interdisciplinary Journal, 2026)
The rapid development of digital technology has opened significant opportunities for information access, while simultaneously worsening the phenomenon of hoax dissemination on social media. Data from the Ministry of Communication and Information Technology reveals that 12,547 hoax contents were handled between August 2018 and 2024, reflecting the severity of this threat to society. This study aims to examine the concept of tabayyun in the hadiths of Prophet Muhammad SAW and its relevance as an ethical solution to combat the spread of hoaxes in the digital era. The research employs a qualitative approach using library research methodology and thematic (maudhu’i) analysis of primary sources including the Qur’an and hadith collections, as well as secondary sources such as scientific journals and relevant books. The findings indicate that the concept of tabayyun, rooted in QS. Al-Hujurat verse 6 and reinforced by several prophetic hadiths, constitutes an epistemic and ethical principle that mandates information verification before acceptance and dissemination. The hadiths of tabayyun, including the prohibition of conveying everything one hears (HR. Bukhari-Muslim) and the exhortation to speak good or remain silent (HR. Bukhari), thematically form a comprehensive framework of Islamic information literacy. Therefore, the values of tabayyun are highly relevant for implementation as a foundation for digital literacy ethics in addressing the challenges of hoaxes in today’s social media era.